MANAJEMEN ASUHAN EBIDANAN REMAJA PADA Nn “S” DENGAN DISMINORHEA PRIMER DI POLI KEBIDANAN DAN KANDUNGAN RS ISLAM FAISAL MAKASSAR TAHUN 2021 - Risky Amelia; Ferawati Taherong; Andi Dian Diarfah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction Adolescence is a period of individual life in which psychological exploration occurs to determine self-identity. During adolescence, physical changes would also occur, in which menstruation becomes the most notice worthy element. The problem that is often experienced by women during menstruation is discomfort or severe pain. The pain that arises is known as dysmenorrhea, which consists of two categories, namely primary dysmenorrhea and secondary dysmenorrhea. The most common one is the primary dysmenorrhea, including experiencing severe pain which may interfere daily activities. This research aims to investigate adolescent midwifery care management on Ms. “S” with primary dysmenorrhea at Obstetrics and Gynecology Polyclinic -RSI Faisal Makassar from August 20th to September 21st 202 using Helen Varney’s 7-step midwifery care management approach and house-visit SOAP technique. The result of this research states that adolescents with Primary Dysminorhea, aged 18 years, complained of abdominal pain experienced for 2 days, nausea and vomiting more than 4 times, weakness and respiratory problems, tender breasts and abdominal tenderness and tension. However, ultrasound examination showed no abnormalities. Conclusion The treatment was conducted by giving infusions, drugs and oxygen. It can be concluded that current physical examination on Ms.